2022
DOI: 10.1021/acsagscitech.1c00269
|View full text |Cite
|
Sign up to set email alerts
|

An Alkali-Triggered Polydopamine Modified Mesoporous Silica Nanopesticide for Smart Delivery of Chlorpyrifos with Low Loss

Abstract: The development of nanotechnology provides a feasible and effective way to reduce pesticide loss and improve pesticide utilization. In this study, we created chlorpyrifos-loaded mesoporous silica nanocomposites modified with polydopamine (Cpf-MSNs@PDA) for the smart control of pests. The release of Cpf from the nanocomposite was alkali triggered and temperature dependent, guaranteeing the sustained and steady effectiveness of the active constituent with prolonged persistence time. The modification with PDA end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Mythimna separata belonged to the order Lepidoptera , of which the environment in the midgut was generally basic 33 . As illustrated in Figures 5–7, incorporating into the nanoparticle reduced the release of EB, especially in basic environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mythimna separata belonged to the order Lepidoptera , of which the environment in the midgut was generally basic 33 . As illustrated in Figures 5–7, incorporating into the nanoparticle reduced the release of EB, especially in basic environment.…”
Section: Resultsmentioning
confidence: 99%
“…Mythimna separata belonged to the order Lepidoptera, of which the environment in the midgut was generally basic. 33 As illustrated in Figures 5-7, incorporating into the nanoparticle reduced the release of EB, especially in basic environment. The increase of the insecticidal activity of the nanoformulation was thus attributed to the enhancement in the penetrating ability of nanoparticles through the cell membrane of the insect.…”
Section: Insecticidal Activity Of Eb@sa-ctab Nanoformulationmentioning
confidence: 97%
“…The PBS with a pH = 5.5 was adjusted using an HCl solution. [ 40 ] Then the samples were incubated in a constantly shanking incubator at 25°C at 100 rpm. At specified time intervals, 0.5 mL of the sample was taken out for centrifugation at 13,000 rpm for 5 min and then the supernatant was analyzed by LC‐MS to determine the concentrations of BAC and 2‐MIM in the solution.…”
Section: Methodsmentioning
confidence: 99%
“…To study the antiwashing properties of MSN-delivered pesticides, Kan and co-workers 97 conducted a simulation study to investigate the rain erosion loss of chlorpyriphos (Cpf) and polydopamine-coated MSN loaded with chlorpyriphos (MSN-PDA@Cpf) from rice leaf. They utilized an acid buret as a rainwater generator.…”
Section: Improved Pest Control Efficacymentioning
confidence: 99%
“…Several studies reported faster release of pesticide from surface-functionalized PSNs influenced by alkaline pH. ,,,, Gao and co-workers coated the surface of abamectin-loaded HSN with poly­(glycidyl methacrylate- co -acrylic acid) (P­(GMA-AA)) to investigate its pH-dependent release. The cumulative release of abamectin from HSN-(P­(GMA-AA))@Aba at pH values of 5 and 7 were 14% and 13%, respectively, after 15 days, whereas 87% of Aba released at pH 10 on the same day, indicating a base-triggered release of pesticide (Figure b).…”
Section: Porous Silica Nanomaterials (Psns) For Pesticide Deliverymentioning
confidence: 99%